Gastric cancer—a clinicopathological study in a tertiary care centre of North-eastern India - Barad, Arun Kumar; Mandal, Sanjeet Kumar; Harsha, Hiriyur S; Sharma, Birkumar M.; Singh, Th Sudhirchandra (Journal of Gastrointestinal Oncology; Vol 5, No 2 (April 25, 2014): Journal of Gastrointestinal Oncology, 2014)
Background: The incidence of gastric cancer varies in different parts of the world and among various ethnic groups. It remains the fifth most common cancer among males and seventh most common cancer among females in India. Materials and methods: We conducted a retrospective study using the data base of 158 patients of primary gastric cancer diagnosed in the Department of Surgery at Regional Cancer Centre, RIMS, Manipur, India from July 2009 to June 2013. Results: Our study revealed a male to female ratio of 2.16:1, distribution of age varied from 28 to 91 years. Majority of the men were in the age group of more than 60 years (45.37%) and majority of females were of 51-60 years (44%). Nearly 7.6% patients had a positive family history. Dietary history of intake salted, fermented fish was present in 67.7% of patients, whereas history of consumption of smoked meat was found in 77.8% of patients. Only 27.8% of patients in our study had history of regular consumption of fresh fruits. About 35.4% of the patients had poor drinking water source. Nearly, 67.6% of males and 44% of females had smoking history. Combined consumption of alcohol and smoking was present in 33.5% of patients. Vague abdominal discomfort was the most common presenting symptom in 61.4% of patients. The most common site of gastric cancer in our study was antrum (50.6%) followed by cardia (17.1%). The most common histological type was adenocarcinoma (95.6%). Most of our patients presented in locally advanced stage (62.7%). Conclusions: Our analysis suggests that poor dietary habits such as smoked mead, dried fish and excessive use of tobacco are associated with high occurrence of gastric cancer in this part of the India. Increasing the awareness regarding the aetiology and varied clinical presentation among general population and health providers is needed for prevention and early detection.